PENGARUH PENDEKATAN PEMBELAJARAN AIR (AUDITORY INTELLECTUALLY REPETITION ) DENGAN METODEDEMONSTRASI TERHADAP KEMAMPUAN BERKOMUNIKASI DAN KEMAMPUAN BERPIKIR KRITIS SISWA - Ariska, Merry; Fuaddunazmi, Muhammad; Habibi, Habibi (Lensa : Jurnal Kependidikan Fisika, 2016)
This research aims to know the existence effect of AIR (Auditory Intellectually Repetition) learning approach with the demonstration method toward the communication and critical thinking ability. This research includes the experimental research (pretest-postest only control group design) with a populations that are all of students grade VII SMPN 8 Taliwang with number of students 40 peoples, sample of this research there are two class, where class of VII A as a experimental class and class VII B as a control  class. Analysis technique used t-test, ttest  for critical thinking abilities 3,64 greater than ttabelis 2,15, communication skills obtained tvalue(3,33)  thantTabel(2,15). Cause the value ttest is greater than ttabel then Ho is unaccepted and Ha accepted, this means the use of AIR learning approach with the method of demonstration has effects on improvement of communication and critical thinking ability in class of VII SMPN 8 Taliwang.